Innovative Methods for Developing Aesthetic and Creative Thinking in Visual Arts Education - Ismoilov Otabek Shavkat o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines innovative methods for developing students’ aesthetic and creative thinking in visual arts education. It discusses the use of interactive lessons, project-based learning, and digital tools to enhance students’ visual thinking, artistic perception, and engagement with art. The study highlights the importance of student-centered pedagogy, creative learning environments, and the integration of traditional and modern art forms to foster aesthetic awareness and originality.